FUZZY LOGIC MAMDANI PENERIMAAN SEMBAKO UNTUK KELUARGA MISKIN - Akbar, Muhammad Jastika Haryalda (Jurnal Sistem Informasi Kaputama (JSIK), 2020)
Poverty is one of the fundamental problems that is the center of attention of the Indonesian government. To improve the coordination of poverty reduction, the Government issued Presidential Regulation Number 15 of 2010 concerning the Acceleration of Poverty Reduction which is a revision of Presidential Regulation Number 13 of 2009 concerning Poverty Reduction Coordination. Indonesia is an agricultural country, the average income derived from agriculture. One of the most advanced agricultural fields is rice, which produces rice as a staple food. The large number of Indonesian citizens causes the domestic rice harvest to be insufficient to meet the needs of its citizens, thus requiring additional supplies from abroad. This causes food shortages, especially for poor families. To improve the stability of Indonesia's economy, the Government is trying various ways by distributing basic food items one of the policies taken by the government is by issuing the Republic of Indonesia's presidential regulation number 63 of 2017 concerning the distribution of non-cash social assistance. Calculations on this decision support system are then used a method, the mamdani fuzzy logic method. Fuzzy logic mamdani method from the point of rule evaluation to determine the basic food recipients for poor families. In determining the nine basic food recipient parameters using fuzzy logic, the input variable is divided into 4 namely age, income, home conditions and number of children.